(untitled) (Iranian Journal of Kidney Diseases, 2021)
Introduction. The mutational changes in Polycystin-1(PC-1) encoded by PKD1 gene is the main cause of Autosomal Dominant Polycystic kidney disease (ADPKD). The pathological changes in renal epithelial cells and multiple cyst formation occur due to activation of cascade of signalling pathways and membrane renal transporters (RTs). Our study have focused on the identification, of different RTs, their interactions with Polycystin-1 and other selected target proteins to find out their role in pathogenesis. Methods. In this study, various RTs protein sequences were identified and retrieved from NCBI’s GenBank and UniProt. RTs were categorized according to different nephronal segmenta as per their functional information retrieved from UniProt and Transpoter databases. Further, sequences were subjected for interaction network analysis in String database and Cytoscape 3.7.2. Different interactions including experimentally validated were identified and can be further validated through in vivo methods. Results. The cross talk between different RT, Polycystin-1 and other sequences were analysed. The various pathways of the interaction with PC-1 were categorised. The total number of 119 nodes and 769 edges interactions were generated. The results were visualized and cross verified with other databases in cytoscape. Conclusion. The cross signalling of PKD1 with SCNN1A, SCNN1G, SLC12A1, AVPR2 shows their importance in the cyst formation and in pathogenesis of ADPKD.